Analisis Grafik Baber Jhonson Berdasarkan Sensus Harian Rawat Inap di Rumah Sakit Khusus Jiwa Soeprapto Bengkulu - Dhaniesty Wijaya, Angga; Rikawati, Ade; Heltiani, Nofri (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2021)
The daily inpatient census is a collection of patient data entering and leaving the inpatient room. The daily census data obtained from each treatment room will be processed, so that later it will get the parameters BOR (Bed Occupancy Rate), AvLos (Average Length Of Stay), TOI (Turn Over Interval), BTO (Bed Turn Over). Present in the formulir of Barber Johnson Graph. The purpose of this study was to determine the calculation of the Barber Johnson chart indicator based on the daily census of inpatients at RSKJ Soeprapto Bengkulu in 2017. The type of research used was descriptive observational with a cross-sectional design, the population in this study was inpatient data recorded at the SHRI. in January-March 2017, totaling 560 patients, with a total sample of the existing population, total sampling. Using secondary data, processed univariately. This research was conducted from July to August 2017 at the medical record unit of RSKJ Soeprapto Bengkulu. The results of univariate analysis, from the calculation of hospital service indicators, the BOR value of IPC room was (60.9%) according to standard, Rajawali (27.38%) not according to standard, Orchid (60.33%) according to standard. The AvLos value of IPC space (2.57 days) was according to the standard, Rajawali (5.52 days) was according to the standard, Orchid (14.22 days) was not up to the standard. BTO value of IPC room (18.8 times) was not up to standard, Rajwali (3.15 times) was not up to standard, Orchid (3.32 times) was not up to standard. TOI value of IPC room (1.9 days) was up to standard, Rajwali (24.57 days) is not up to standard, Orchid (11.42 days) is not up to standard. It is expected that health workers, especially medical records, fill out the Inpatient Daily Census (SHRI) form completely so that Barber Johnson charts can be made so that the efficiency of hospital management is known.